Analysis of the stability behavior of cross bracings in transmission towers based on experiments and numerical simulations. (April 2023) - Li, Yan; Yan, Zhitao; Zhou, Dongping; Ren, Qingyang; Hua, Chao; Zhong, Yongli
Abstract: Angle steel towers are widely used in various transmission lines owing to their convenient connections, easy availability, simple production processes, and high efficiencies. Cross bracings play an important role in resisting wire tension, wind, and snow loads as the main support components ensuring the stability of an angled steel tower. Thus, an analysis of the buckling resistance of cross bracings is significant in improving the bearing capacity of transmission towers. In this study, full-scale tests of equal-leg and unequal-leg angles in planar tower sections were conducted. The influence of the axial force ratio on the stability of a cross bracing was studied based on numerical simulations and compared with the current codes. The results revealed that the failure mode of an equal-leg angle cross bracing was always out-of-plane buckling, whereas the final failure mode of an unequal-leg angle steel cross bracing could be out-of-plane buckling or both out-of-plane and in-plane co-buckling. With an increase in the axial force ratio, the buckling resistance of the cross bracing decreased rapidly, with over 40% decline in the amplitude. The buckling resistance of the unequal-leg angle was approximately 20% higher than that of the equal-leg angle at all axial force ratios. Compared with the current codes for tower structures, we discovered that the code values and finite-element results were considerably different. Notably, the calculation methods of ASCE 10-15 and EN1993-3-1 neglect the variation in the effective length with the axial force ratio. Although DL/T 5154-2012 considers the effect of the axial force ratio, the values are all greater than the finite-element results. The findings of this study can help elucidate the cross bracing stability in angle steel lattice towers. Highlights: Full-scale tests of cross bracings in planar tower sections are carried out. The buckling failure modes of cross bracings are mainly out-of-plane buckling. Unequal-leg angle cross bracing can replace equal-leg angle in transmission tower. Buckling resistance of cross bracing decreases with increasing axial force ratio. There are great differences among the codes values and the finite-element results.